The inter-connection of sports bra design attributes and elderly women's perceptions - Jie Zhou; Qiwen Emma Lei; Qian Mao; Aosi Wang; Joanne Yip; Jun Zhang (Fashion and Textiles, 2023)
Abstract As a sports facility category, a sports bra is regarded as an enabling technology garment with advanced functions and new cultural meanings. Women, particularly elderly women, are encouraged to wear a sports bra during physical activity because wearing a sports bra can not only prevent them from exercise-induced injuries but also increase the acceptance of their bodies. However, most studies usually targeted younger women. The requirements and expectations of elderly women on sports bras differ from younger individuals. Hence, this study aims to advance and explore the design demands, providing insights into age-friendly sports bra design by using more permeable physical and psychological boundaries based on conceptual frameworks. The sports bra evaluation words were extracted and calculated to construct the network. The appearance frequency of keywords, closeness centrality, betweenness centrality, and interconnection between every pair of words were illustrated and analyzed by using semantic-based network analysis. Network analysis deduced that the discomfort of sports bras was closely related with the support, tightness, cup design, and strap design. Beside, thermal management contributes significantly to the comfort. The outlook of a sports bra was associated with cup design. The Page-rank result showed that cup, tightness, hot, straps and quality were the top five important design attributes. The unobservable mechanisms underlying the keywords provide an alternative model, which can help to explore the key improvements for sports bra design.